A critical review on FE-based methods for mesh stiffness estimation in spur gears. (July 2021) - Natali, Caterina; Battarra, Mattia; Dalpiaz, Giorgio; Mucchi, Emiliano
Highlights: A critical review of mesh stiffness calculation methods for spur gears is performed. The theoretical background of the methods is exposed. Critical aspects of the methods are pointed out and discussed. The methods are compared in terms of results accuracy and computational time. Abstract: Several methodologies for the mesh stiffness calculation in spur gears have been found in the literature, in the last decades. Based on a bibliographical analysis and the research activities of the authors, attention has been devoted to three methodologies, which appeared as the most employed and cited. A critical review of such methodologies, FE-based method, hybrid analytical-FE method, and analytical approach, has been undertaken, highlighting some crucial aspects regarding the mesh stiffness estimation process. Within this framework, useful information related to the critical choice of parameters needed for the implementation of the methods are presented, in order to provide further guidelines for their application. Furthermore, the methods are compared in terms of results accuracy and computational time for full blank and lightweight gears. This comparison leads to useful guidelines regarding the definition of the most suitable approach depending on the specific requirements. Finally, two variants of an examined hybrid method are presented. They are based on linear, nonlinear FE analyses and analytical formulation. Their purpose is to compare the use of different analytical formulations against the FE formulation for the computation of the local deformation of gear teeth.